Hematological Studies on Malnad Gidda Breed of Cattle in Karnataka - Narynaswamy, Gowda M; Veena, T; Krishnaswamy, A; Nagaraja, CS; Sridhar, NB; Ganesh, K; kalmath, GP (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study was conducted to establish the base line hematological values in Malnad Gidda cattle during winter and summer seasons under the agro-climatic condition of Western Ghats of Karnataka. Thirty healthy Malnad Gidda cattle divided into five groups based on age, sex and lactation. The mean values of TEC, Hb, PCV, ESR, TLC and eosinophil per cent were significantly (P<0.05) higher in adult animals than young animals in both sexes. But, MCV was significantly (P<0.05) higher in young compared to adult animals. The mean values of MCH, MCHC, neutrophil, basophil, monocyte and lymphocyte per cent did not vary significantly among the age groups and among the gender. The mean values of all the above parameters between sexes within age groups and between the seasons were not significantly different. The established hematological values in present study could be used as reference values in Malnad Gidda breed reared under similar climatic and environmental conditions.